Sri Guru Gobind Singh's Shabad hazare, the ten swaiyas & 33 swaiyas - Gobind Singh, Guru, 1666-1708 (Gurbani parchar series ; no. 5., 1967)
Parallel translation of Sikh-religious verse in Old Panjabi taken from the Daswen Pādshāh kā Granth, to be recited, chiefly during the Sikh baptismal ceremony; with interpretive notes.